Women's Wages in Women's Work: A U.S./Canada Comparison of the Roles of Unions and “Public Goods” Sector Jobs - Baker, Michael; Fortin, Nicole M (American Economic Review, 1999)
Women's Wages in Women's Work: A U.S./Canada Comparison of the Roles of Unions and "Public Goods" Sector Jobs by Michael Baker and Nicole M. Fortin. Published in volume 89, issue 2, pages 198-203 of American Economic Review, May 1999